Resistance analysis of the rice variety Huaidao 5 against root-knot nematode Meloidogyne graminicola - Hui FENG; Can-rong ZHOU; Feng ZHU; Xiu-hu LE; De-dao JING; DALY Paul; Dong-mei ZHOU; Li-hui WEI (Journal of Integrative Agriculture, 2023)
Meloidogyne graminicola has emerged as one of the most destructive plant-parasitic nematodes affecting rice (Oryza sativa) production worldwide. Resistance to M. graminicola in rice could be the most effective option for its management. However, sources of germplasm with resistance to M. graminicola in rice remain limited. Here, we describe the root attraction, gall formation and genetic analysis of the resistance to M. graminicola in the rice variety Huidao 5. A nematode attraction assay showed that second-stage juveniles (J2s) of M. graminicola were attracted at the root tip of Huaidao 5 within 8 h without a significant reduction in attraction compared to the susceptible rice variety Nanjing 9108. Microscopic observation of the infection revealed that the J2s invaded root tissues 12 h after inoculation, but their subsequent movement to the root tip was hindered in Huaidao 5, resulting in decreased nematode number compared to Nanjing 9108. Additionally, we used the soil and hydroponic culture systems to simulate upland and flooding conditions in the paddy fields respectively, and found that gall number was significantly reduced, and nematode development was clearly suppressed in Huaidao 5. To investigate the genetic basis of this resistance, cross breeding was performed between the Huaidao 5 and Nanjing 9108 varieties. There was no reduction in the resistance of the F1 offspring to M. graminicola in the greenhouse or field trials, suggesting that a dominant gene could control resistance in Huaidao 5. In summary, this study provides a detailed characterization of a novel source of resistance to M. graminicola in rice, which is of great potential for use in crop breeding.